Cycloaddition Reaction between Dibromovinylidene and Formaldehyde: A Density Functional Theory Study - Dai, Guo-Liang; Yan, Hua; Zhong, Ai-Guo; Wang, Chuan-Feng (Asian Journal of Chemistry, 2010)
The mechanism of the cycloaddition reaction between dibromovinylidene and formaldehyde has been characterized by density functional theory. All the stationary points were determined at the B3LYP/6-311++G** level of the theory. Single point CCSD(T)/6-311++G** calculation was used to get accurate energy. We have also calculated the changes of thermodynamic functions and the quality of kinetic properties for this reaction at different temperatures by using statistical thermodynamics method and transition-state theory. The results show that the present reaction has two major pathways. The first one brings about a three-membered ring product (P1) with a low energy barrier of 45.9 kJ/mol (14.6 kJ/mol relative to reactants). The latter one can generate a four-membered ring product P2, this is a spontaneous and great exothermic reaction. In view of dynamics and thermodynamics, it is between 500-1000 K that the major reaction may have not only the larger spontaneous tendency and equilibrium constant but also quicker reaction rate.